A New Way of Monitoring the Quality of Urban Life - Eduardo Lora; Andrew Powell (Inter-American Development Bank (IDB), 2011)
This paper proposes a methodology to resolve the problems that result from using a combination of objective and subjective information in evaluating urban quality of life. The paper further suggests techniques to identify and rank issues of potential importance for urban dwellers. In order to combine objective and subjective information in a coherent manner and focus on the most relevant dimensions of the quality of life in a city or neighborhood, the paper attempts to exploit the complementary nature of two approaches: the hedonic approach, which employs market prices for housing, and the life satisfaction approach, which addresses subjective well-being. Results using both approaches in selected Latin American cities are discussed and compared. The paper concludes with a discussion of potential uses of the two-pronged methodology for policy analysis.
Keywords: D19; H41; H42; I31; 330